Tumor del seno endodermal extragonadal en la infancia. Reporte de dos casos. - SÁNCHEZ LIHON, Juvenal; CASAVILCA ZAMBRANO, Sandro; GARCIA MADRID, Jorge; KLINGE CASTRO, German (Revista Médica Herediana, 2013)
We report two cases of extragonadal pelvic endodermal sinus tumor diagnosed at the Departament of Pediatric of the National Institute of Neoplastic Diseases and discuss the clinical presentation, differential diagnosis and pathologic study.